For the love of Pete : a novel - Marino, Jan. (Boston : Little, Brown, 1993)
When her grandmother moves into a nursing home, twelve- year-old Phoebe sets out in the old family car with three of Gram's servants, on a search for the father who abandoned her at birth
Accelerated Reader AR
Keywords: Household employees -- Fiction; Fathers and daughters -- Fiction